Adaptação do comportamento animal e mundos emergentes - DUBOIS, Michel Jean (2016)
We discuss the implications of the concept of adaptation, which is a key notion for the classical theory of evolution. Instead of persisting to consider the organisms as a collection of adapted traits, we propose to study evolution by means of a theoretical frame based on another ontology considering the organisms and the circumstances as totally integrated. The necessary preliminary stage for this reconsideration consists in passing from a prescriptive logic to a proscriptive logic, i.e., from the idea that everything that is not allowed is forbidden, to the idea that what is not forbidden is allowed. The consideration that the living systems specify the world in which they live can modify our way to face adaptive processes.